TTG Mesin Penghalus Pipa Roll Conveyor Pengganti Mesin Bubut Wilayah Surabaya Barat - Mochammad Muchid Muchid; Dwi Yustianto; Subaderi Subaderi; Andianto Wahyu Nugroho (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
The right technology for roll conveyor smoothing machine is in West Surabaya, precisely in Kandangan Village, Benowo District. Mortek Suraindo is a workshop that is engaged in the service and manufacture of aspry spryer machines, car body, silo, and conveyor, which consists of roll and bracket. Mortek Suraindo as a partner in the Community Partnership Program, the dominant activity is the manufacture of roll conveyors, roll conveyors consisting of rollers and brackets. The implementation of making a roller consists of several parts that are in it, namely: pipes, house bearings, 6203 bearings, bearing covers, snap bearings and axles, roller production production there are several parts that are worked out on the grounds of machine inventory and time, the type of work done outside need a lathe for leveling and cleaning the results of welding between pipes with house bearing, this work every 1pc Rp. 7,000 every week can work 200pcs, the price of services is 1 month = Rp. 5,600,000 to cut expenses, the University of Wijaya Putra PKM team made a roll conveyor smoothing machine with a prototype at SolidWork to ensure the success of making the machine, after the roll conveyor smoothing machine was socialized and used for 10 months it was capable of ± 14,000 pcs and able to obtain profits Rp. 21,000,000 and can buy roll conveyor smoothing machines